Randomized controlled study: Comparison of 20% autologous- serum eye drops with unpreserved hypromellose in the treatment of aqueous-tear- deficient dry-eye disease - Simplicio I. Hocson III, MD; Kristine T Lo, MD; Ruben Lim-Bon-Siong, MD (Philippine Journal of Ophthalmology)
Objective: This study evaluated the effectiveness of 20% autologous-serum eye drops versus unpreserved hypromellose in the treatment of patients with aqueoustear-deficient dry-eye disease.